PENGARUH STRUKTUR MODAL, PROFITABILITAS, LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERASI - Satiya Silen; Herlina Lusmeida (Faculty of Economics and Business Universitas Pelita Harapan, 2025)
This study aims to analyze whether capital structure, profitability, and liquidity have a significant impact on dividend policy by testing the role of managerial ownership as a moderating variable. The research is quantitative, using secondary data from a sample of 86 manufacturing companies, totaling 344 observations over the 2019-2022 period. The data was collected using purposive sampling. The analytical method applied is multiple regression analysis, utilizing STATA 17.0 software. The findings show that capital structure has a positive effect on dividend policy, while profitability and liquidity have a negative effect on dividend policy. Furthermore, managerial ownership does not strengthen the positive influence of capital structure, profitability, and liquidity on dividend policy.